Judicialization of Zolgensma in the Ministry of Health: costs and clinical profile of patients - Ana Katheryne Miranda Kretzschmar; Ellen Teixeira; Dayani Galato; Everton Nunes da Silva (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To investigate the costs and profile of patients who have filed a lawsuit against the Ministry of Health for the treatment of spinal muscular atrophy (SMA) with the onasemnogene abeparvovec (Zolgensma®). METHODS This is a cross-sectional, descriptive study with a census design, based on records of lawsuits filed against the Ministry of Health between January 2019 and September 2022. Data was requested from the Ministry of Health via the Access to Information Act. Information was extracted on the epidemiological profile of the beneficiaries of the lawsuits, as well as the expenses spent by the Ministry of Health in cases where the requests were granted. RESULTS 136 lawsuits were identified, of which 113 (83%) were favorable to patients at a cost of R$ 944.8 million in the period analyzed. Demographic (gender and age), clinical (SMA subtypes, use of ventilatory or nutritional support), and lawsuit (type of legal service) characteristics were not associated with the granting of lawsuits. Prior use of medication (nusinersena or ridisplam) was associated with the dismissal of lawsuits. Of the 113 lawsuits granted in favor of patients, only six (5.3%) would meet the criteria currently established by the National Committee for Health Technology Incorporation - Conitec (children up to six months without ventilatory and nutritional support). R$ 146 million was spent on supplying Zolgensma to children over the age of two, which is outside the recommendation contained in the drug's package leaflet. CONCLUSIONS The Ministry of Health incurs a high cost with the judicialization of Zolgensma for SMA, representing 2.45% of total spending on medicines in the Unified Health System, including spending by the three administrative spheres. Some of the lawsuits have been granted in disagreement with the criteria established by health technology assessment agencies and the drug manufacturer's recommendations.